Harmony at Home and School Makes Them Superior in Learning Natural and Social Sciences - Desy Nur Yasinta; Ika Ratnaningrum (Universitas Pendidikan Ganesha, 2024)
In the era of globalization and rapid technological development, the need to produce students who excel in natural and social sciences is becoming increasingly important. Many students still need help achieving optimal academic achievement, which is caused by the lack of holistic support from the home and school environment. Research shows that harmony between the home and school environment plays an important role in shaping students' character, motivation, and positive attitudes towards learning. When parents and educators work together and provide consistent support, students are more likely to develop in natural and social sciences. This study aims to explore the influence of learning interest and learning environment on the learning outcomes of fourth-grade students in science. This study uses a quantitative method with an ex post facto design. The study population was fourth-grade students, with a sample of 66 students selected randomly. Interviews, questionnaires, and recording of learning objectives were used to collect data. Data analysis was carried out using descriptive, simple, and multiple regression techniques. The results showed that learning interest and learning environment significantly influenced learning outcomes in science. Learning interest, which includes awareness, attention, willingness, and pleasure in learning, positively contributes to academic achievement. The learning environment, supported by parental understanding, teaching methods, home conditions, economic situation, cultural background, and relationships between family members, also plays an important role. These findings have practical implications, highlighting the importance of collaboration between teachers and parents in creating a conducive learning environment.